2017
DOI: 10.3415/vcot-16-10-0148
|View full text |Cite
|
Sign up to set email alerts
|

Surgical stabilization of concomitant canine medial patellar luxation and cranial cruciate ligament disease

Abstract: Stifles stabilized using ECS+TTT are more likely to suffer from postoperative complications and a poorer clinical outcome when compared to TTTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…7,8 One study compared the results of ECS þ TTT treated dogs versus dogs treated with a tibial tuberosity transposition (TTT) and advancement. 18 The results of this study showed a 2.7Â increase in complications within the ECS þ TTT group over the tibial tuberosity transposition and advancement group. 18 The average weight in their study population was 23.4 kg.…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…7,8 One study compared the results of ECS þ TTT treated dogs versus dogs treated with a tibial tuberosity transposition (TTT) and advancement. 18 The results of this study showed a 2.7Â increase in complications within the ECS þ TTT group over the tibial tuberosity transposition and advancement group. 18 The average weight in their study population was 23.4 kg.…”
Section: Introductionmentioning
confidence: 63%
“…18 The results of this study showed a 2.7Â increase in complications within the ECS þ TTT group over the tibial tuberosity transposition and advancement group. 18 The average weight in their study population was 23.4 kg. 18 While ECS is a feasible method of repair of cranial cruciate ligament disease in those dogs, it may not be the best choice for dogs with concurrent medial patellar luxation.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…As you will read in this issue of the Journal, there are also other papers related to problems of medial patellar luxation and cranial cruciate ligament disease, as well as various other topics (5,6). I hope you enjoy delving into this new information, and thinking about its implications!…”
mentioning
confidence: 97%